Physiological Overview of the Potential Link between the UPS and Ca2+ Signaling - Dongun Lee; Jeong Hee Hong (MDPI AG, 2022)
The ubiquitin-proteasome system (UPS) is the main proteolytic pathway by which damaged target proteins are degraded after ubiquitination and the recruit of ubiquitinated proteins, thus regulating diverse physiological functions and the maintenance in various tissues and cells. Ca2+ signaling is raised by oxidative or ER stress. Although the basic function of the UPS has been extensively elucidated and has been continued to define its mechanism, the precise relationship between the UPS and Ca2+ signaling remains unclear. In the present review, we describe the relationship between the UPS and Ca2+ signaling, including Ca2+-associated proteins, to understand the end point of oxidative stress. The UPS modulates Ca2+ signaling via the degradation of Ca2+-related proteins, including Ca2+ channels and transporters. Conversely, the modulation of UPS is driven by increases in the intracellular Ca2+ concentration. The multifaceted relationship between the UPS and Ca2+ plays critical roles in different tissue systems. Thus, we highlight the potential crosstalk between the UPS and Ca2+ signaling by providing an overview of the UPS in different organ systems and illuminating the relationship between the UPS and autophagy.